WORKPLACES DRESS CODE: EFFECT AND IMPORTANT - Fadillah Ismail,; Kamilah Ahmad,; Siti Sarawati Johar, (Journal of Islamic, Social, Economics and Development, 2023)
Nowadays, a formal workplace dress code is no longer implemented by many organizations. The employees are being encouraged to dress comfortably as it is believed that this will enhance the performance and productivity. There is quick a number of issues occur even the organization has established a dress code policy for their employee as the dress code was constructing using ambiguous terms like “acceptable”, “professional” without outlining a precise policy. The objective of the study is to discuss why dress code is important in the workplace as well as the positive effect and negative effect of workplace dress code towards an organization. To highlight, this study discussed several factors that make dress code important in the workplace such as ensure pride and responsibility, prioritizes safety and create a great first impression. Moreover, the second part explained and justified the positive effects of workplace dress code like enable employees to save more money, reduces social conflict and pressure, enhances the image of an organization and equality and professionalism as well as the negative effects like kills down creativity, arises discomfort for some employee, outdated concept and dress codes are anachronism. The researcher discussed on the best company which has dress code policy as benchmark which are Amazon and Walmart. Hence, this research suggested through meet with the employees privately and send out reminders when necessary could help to eliminate dress code issue in the workplace.